Protective film for blade of wind power generator, blade of wind power generator, and wind power generator

JP2025033806APending Publication Date: 2025-03-13DAI NIPPON PRINTING CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023139796
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-30
Publication Date
2025-03-13

AI Technical Summary

Benefits of technology

【0010】 本開示においては、耐久性が良好であるブレード用保護フィルムを提供できるという効果を奏する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025033806000001_ABST
    Figure 2025033806000001_ABST
Patent Text Reader

Abstract

To provide a protective film for a blade of a wind power generator characterized by excellent durability.SOLUTION: The present disclosure provides a protective film for a blade of a wind power generator, the protective film having a protective layer containing a polyolefin resin, and an adhesive layer disposed on one surface of the protective layer, wherein the protective layer has a tensile elastic modulus of 5-35 MPa inclusive.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a protective film for wind turbine blades, a wind turbine blade, and a wind turbine. [Background technology]

[0002] The blades of wind power generation equipment are exposed to ultraviolet rays from sunlight, wind, rain, snow, hail, lightning, seawater, gas, sand, dust, and other debris. The blades of wind power generation equipment may also be affected by collisions with birds, insects, and flying objects. As described above, the blades are exposed to harsh environments, and as a result of long-term use, defects such as damage, deformation, surface contamination, and surface peeling occur. In addition, the blades rotate at high speeds, which increases the possibility of damage, deformation, surface contamination, and surface peeling. These defects lead to a decrease in power generation efficiency. In the worst case, the blades may break or fall.

[0003] Therefore, in order to protect the blade, a technique has been proposed in which a protective film or protective cover is placed on the surface of the blade (Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2012 / 102294 [Patent Document 2] Special Publication No. 2018-503775 Summary of the Invention [Problem to be solved by the invention]

[0005] Patent Document 2 discloses a protective cover made of a polyurethane material. However, polyurethane resins are prone to deterioration over time. Therefore, protective films and protective covers made of polyurethane resins have a problem in that their performance deteriorates due to deterioration over time.

[0006] The present disclosure has been made in consideration of the above-mentioned circumstances, and has a main object to provide a protective film for wind turbine blades having good durability. [Means for solving the problem]

[0007] One embodiment of the present disclosure provides a protective film for wind turbine blades, comprising a protective layer containing a polyolefin resin and an adhesive layer disposed on one side of the protective layer, the protective layer having a tensile modulus of elasticity of 5 MPa or more and 35 MPa or less.

[0008] Another embodiment of the present disclosure provides a blade for a wind turbine generator having the above-described blade protective film on a surface thereof.

[0009] Another embodiment of the present disclosure provides a wind turbine generator including the blade described above. Effect of the Invention

[0010] The present disclosure has an effect of providing a blade protection film having good durability. [Brief description of the drawings]

[0011] [Figure 1] 1 is a schematic cross-sectional view illustrating a protective film for wind turbine blades according to the present disclosure. [Diagram 2] 1 is a schematic cross-sectional view illustrating a protective film for wind turbine blades according to the present disclosure. [Diagram 3] 1A and 1B are schematic perspective and cross-sectional views illustrating a blade of a wind turbine power generation device according to the present disclosure. [Figure 4] 1 is a schematic diagram illustrating a wind power generation device according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The following describes the embodiments of the present disclosure with reference to the drawings. However, the present disclosure can be implemented in many different forms, and is not to be construed as being limited to the description of the embodiments exemplified below. In addition, the drawings may be schematic in terms of the width, thickness, shape, etc. of each part compared to the actual form in order to make the explanation clearer, but these are merely examples and should not be used to limit the interpretation of the present disclosure. In addition, in this specification and each figure, elements similar to those described above with respect to the previous figures may be given the same reference numerals, and detailed explanations may be omitted as appropriate.

[0013] In this specification, when describing a mode in which another component is disposed on a certain component, the term "above" or "below" includes both a case in which another component is disposed directly above or below a certain component so as to be in contact with the component, and a case in which another component is disposed above or below a certain component with another component interposed therebetween, unless otherwise specified. In addition, in this specification, when describing a mode in which another component is disposed on the surface of a certain component, the term "on the surface side" or "on the surface" includes both a case in which another component is disposed directly above or below a certain component so as to be in contact with the component, and a case in which another component is disposed above or below a certain component with another component interposed therebetween, unless otherwise specified.

[0014] In this specification, the term "film" also includes a member called a "sheet."

[0015] The protective film for wind turbine blades, the wind turbine blades, and the wind turbine according to the present disclosure will be described in detail below.

[0016] A.Protective film for wind turbine blades The protective film for wind power generation device blades in the present disclosure has a protective layer containing a polyolefin resin and an adhesive layer arranged on one side of the protective layer, and the tensile modulus of the protective layer is 5 MPa or more and 35 MPa or less.

[0017] In this specification, the term "protective film for wind turbine blades" may be abbreviated to simply "protective film".

[0018] Fig. 1 is a schematic cross-sectional view illustrating a protective film according to the present disclosure. The protective film 10 in Fig. 1 has a protective layer 1 containing a polyolefin resin and an adhesive layer 2 disposed on one surface of the protective layer 1. The tensile modulus of elasticity of the protective layer 1 is within a predetermined range.

[0019] Here, it is known that polyurethane resins are used as conventional protective films. However, polyurethane resins tend to decompose gradually with long-term use, and the performance of the protective film may deteriorate due to aging. In the present disclosure, a polyolefin resin is used for the protective layer of the protective film, so that such defects can be suppressed. In addition, the inventors of the present disclosure have studied and found that a protective film having a protective layer containing a polyolefin resin has good durability compared to a protective film having a protective layer containing a polyurethane resin, as described in the Examples section below.

[0020] Furthermore, the inventors of the present disclosure have studied the durability of a protective film having a protective layer containing a polyolefin resin, and have found that when a relatively soft polyolefin resin is used among polyolefin resins, the erosion resistance is higher than when a relatively hard polyolefin resin is used. This is thought to be because the relatively soft protective layer absorbs impacts, thereby suppressing the occurrence of erosion. In other words, in the present disclosure, the tensile modulus of the protective layer is within a predetermined range, thereby making it possible to increase durability.

[0021] In addition, in the present disclosure, since the tensile modulus of the protective layer is within a predetermined range, the ability to conform to the curved surface of the blade can also be improved.

[0022] In general, polyolefin resins tend to have a lower density than polyurethane resins. Therefore, by using a polyolefin resin for the protective layer of the protective film, the protective layer can be made lighter, and the protective film can be made lighter. This prevents the blade from becoming heavier due to the protective film, and suppresses a decrease in power generation efficiency.

[0023] Furthermore, generally, polyurethane resins are hydrophilic, whereas polyolefin resins tend to be hydrophobic. Therefore, by using a polyolefin resin for the protective layer of the protective film, adhesion of moisture can be suppressed. This can suppress condensation, rain, snow, and ice caused by temperature changes on the blades. This can suppress a decrease in power generation efficiency. Also, it can suppress the infiltration of moisture into the inside of the blades. This can suppress corrosion and damage of the blades, and a decrease in insulation of the electrical system.

[0024] Therefore, the protective film according to the present disclosure is suitable as a protective film for use on the blades of wind turbine generators.

[0025] It is also important to inspect the blades of the wind power generation device periodically and, if necessary, perform maintenance such as repairs. In the present disclosure, the tensile modulus of the protective layer is within a predetermined range and is soft, so that not only the workability when attaching the protective film to the surface of the blade but also the workability when peeling the protective film from the surface of the blade when replacing the protective film can be improved. Furthermore, in the present disclosure, the durability of the protective film is good, so that peeling failure due to deterioration of the protective film can be suppressed.

[0026] Hereinafter, each configuration of the protective film in the present disclosure will be described.

[0027] 1.Protective layer The protective layer in the present disclosure is a member containing a polyolefin resin.

[0028] (1) Physical properties of the protective layer (a) Tensile modulus In the present disclosure, the tensile modulus of the protective layer is 35 MPa or less, may be 30 MPa or less, may be 20 MPa or less, or may be 15 MPa or less. When the tensile modulus of the protective layer is within the above range, the protective layer tends to be soft, stretchable, and difficult to deform. Therefore, when wind, rain, snow, hail, hail, seawater, sand, dust, dirt, birds, insects, flying objects, etc. collide with the surface of the blade having the protective film, the protective layer of the protective film can absorb the impact. Therefore, the occurrence of erosion can be suppressed. In addition, the ability to follow the curved surface of the blade can be improved. On the other hand, the tensile modulus of the protective layer is 5 MPa or more, may be 7 MPa or more, or may be 10 MPa or more. If the tensile modulus of the protective layer is too low, the protective layer may become too soft, which may reduce the erosion resistance or make it difficult to handle the protective film. Specifically, the tensile modulus of the protective layer is 5 MPa or more and 35 MPa or less, optionally 5 MPa or more and 30 MPa or less, optionally 7 MPa or more and 20 MPa or less, or optionally 10 MPa or more and 15 MPa or less.

[0029] The tensile modulus is measured using a tensile tester in accordance with ISO 527-3:2018. The tensile modulus is the slope of the stress-strain curve calculated by the least squares method between the two points of 5% strain and 10% strain. The specific measurement conditions are shown below.

[0030] <Measurement conditions> Test piece: rectangular - Test piece size: width 10mm, length 80mm ·Distance between gauge lines: 25mm Pulling speed: 100mm / min Test conditions: Temperature 25℃, humidity 50%RH Number of test pieces: Measurement is performed on three test pieces, and the arithmetic average value is used.

[0031] When measuring the tensile modulus of the protective layer, the adhesive layer is removed from the protective film, and the protective layer is taken out. As a method for removing the adhesive layer, a method of dissolving the adhesive layer with a solvent can be used. As the solvent, the solvent contained in the adhesive composition used to form the adhesive layer can be used.

[0032] (b) Tensile breaking stress In the present disclosure, the tensile breaking stress of the protective layer is, for example, 5 MPa or more, may be 7 MPa or more, or may be 10 MPa or more. When the tensile breaking stress of the protective layer is in the above range, durability can be improved. On the other hand, the tensile breaking stress of the protective layer is, for example, 35 MPa or less, may be 30 MPa or less, or may be 20 MPa or less. If the tensile breaking stress of the protective layer is too large, the protective film becomes difficult to stretch, and the ability to follow the curved surface of the blade may decrease. Specifically, the tensile breaking stress of the protective layer is 5 MPa or more and 35 MPa or less, may be 7 MPa or more and 30 MPa or less, or may be 10 MPa or more and 20 MPa or less.

[0033] The tensile stress at break is measured using a tensile tester in accordance with ISO 527-3:2018. The tensile stress at break is the stress at which the test piece breaks. The tensile test for measuring the tensile stress at break is the same as the tensile test for measuring the tensile modulus of elasticity described above.

[0034] (c) Tensile elongation at break In the present disclosure, the tensile elongation at break of the protective layer is, for example, preferably 800% or more, may be 1000% or more, or may be 1200% or more. When the tensile elongation at break of the protective layer is in the above range, durability can be improved. On the other hand, the upper limit of the tensile elongation at break of the protective layer is not particularly limited, but may be, for example, 3500% or less, 3000% or less, or 2500% or less. Specifically, the tensile elongation at break of the protective layer is 800% or more and 3500% or less, 1000% or more and 3000% or less, or 1200% or more and 2500% or less.

[0035] The tensile elongation at break is measured using a tensile tester in accordance with ISO 527-3:2018. The tensile elongation at break is the elongation at break of the test piece. The tensile test for measuring the tensile elongation at break is the same as the tensile test for measuring the tensile modulus described above.

[0036] (d) Type A durometer hardness In the present disclosure, the type A durometer hardness of the protective layer is, for example, preferably 85 or less, may be 80 or less, or may be 75 or less. When the type A durometer hardness of the protective layer is within the above range, the protective layer tends to be relatively soft. Therefore, the protective layer of the protective film can absorb the impact caused by the collision with the blade, so that the occurrence of erosion can be suppressed. In addition, the conformability to the curved surface of the blade can be improved. On the other hand, the type A durometer hardness of the protective layer is, for example, 60 or more, may be 65 or more, or may be 70 or more. If the durometer A hardness of the protective layer is too low, the protective layer may become too soft, and the erosion resistance may decrease, or the handling of the protective film may become difficult. Specifically, the type A durometer hardness of the protective layer is 60 or more and 85 or less, may be 65 or more and 80 or less, or may be 70 or more and 75 or less.

[0037] Type A durometer hardness is measured using a hardness tester in accordance with JIS K6253-3:2012. However, when stacking test pieces for measurement, the number of test pieces stacked is not limited. For example, when the thickness of the protective layer is 300 μm, 20 test pieces are stacked. The specific measurement conditions are shown below.

[0038] <Measurement conditions> Test piece thickness: 6mm Test conditions: 23℃, 50% RH Measurement time: 3 seconds

[0039] (e) Unit Weight In the present disclosure, the unit weight of the protective layer is, for example, 900 g / m 2 Less than 650 g / m 2 or less, 450 g / m2 or less. When the unit weight of the protective layer is within the above range, the protective layer tends to be light and thin. Therefore, the weight of the protective film can be reduced. As a result, the weight of the blade having the protective film can be prevented from increasing, and a decrease in power generation efficiency can be suppressed. On the other hand, the lower limit of the unit weight of the protective layer is not particularly limited, and may be, for example, 40 g / m 2 More than 65g / m 2 or more, and 2 Specifically, the unit weight of the protective layer may be 40 g / m 2 More than 900g / m 2 Less than 65 g / m is preferred 2 More than 650g / m 2 or less, 85 g / m 2 More than 450g / m 2 It may be the following.

[0040] The unit weight is the weight per unit area. The unit weight is calculated by the following method. First, the protective layer is cut into a 10 cm square and the weight is measured. Next, the measured weight is multiplied by 100 and expressed in g / cm. 2 From g / m 2 When measuring the unit weight of the protective layer, the adhesive layer is removed from the protective film, and the protective layer is taken out. The method for removing the adhesive layer is as described above.

[0041] (f) Water vapor permeability In the present disclosure, the water vapor permeability of the protective layer is, for example, 15.0 g / (m 2 24h) or less is preferable, and 10.0g / (m 2 24h) or less is more preferable, and 5.0g / (m 2 ·24h) or less is more preferable, and 3g / (m 2 24h) or less, and 1g / (m 2 The water vapor permeability of the protective layer may be within the above range, thereby preventing moisture from penetrating into the blade. This prevents corrosion and damage to the blade and deterioration of the insulation of the electrical system. On the other hand, there is no particular lower limit for the water vapor permeability of the protective layer.

[0042] The water vapor permeability is measured using a water vapor permeability measuring device in accordance with JIS K7129-2:2019. For example, the water vapor permeability measuring device "PERMATRAN-w 3 / 33" manufactured by MOCON is used. First, a test piece of a predetermined size is cut out from the protective layer. Next, the test piece is mounted between the upper and lower chambers of the water vapor permeability measuring device. At this time, if the protective layer is multi-layered, the test piece is mounted in the water vapor permeability measuring device so that the surface of the protective layer opposite the adhesive layer is the high humidity side (water vapor supply side). Next, the measurement is performed under conditions of a temperature of 40 ° C. and 90% RH. Measurement is performed with three test pieces, and the arithmetic average value is adopted. When measuring the water vapor permeability of the protective layer, the adhesive layer is removed from the protective film and the protective layer is taken out. The method of removing the adhesive layer is as described above.

[0043] In general, polyolefin resins tend to have lower water vapor permeability than polyurethane resins.

[0044] (g) Total light transmittance In the present disclosure, the total light transmittance of the protective layer is, for example, preferably 60% or more, more preferably 65% ​​or more, and even more preferably 70% or more. As described above, it is important to inspect the blades of the wind power generation device periodically and, if necessary, perform maintenance such as repair. If the total light transmittance is within the above range, the transparency is good. Therefore, since the surface of the blade can be visually confirmed through the protective film, it is easy to determine when to replace the protective film.

[0045] Total light transmittance is measured in accordance with ISO 13468-1:1996.

[0046] (h) Water contact angle In the present disclosure, the protective layer is preferably hydrophobic. This can suppress adhesion of moisture to the blade. This can suppress condensation, rain, snow, and ice caused by temperature changes on the blade. This can suppress a decrease in power generation efficiency. In addition, this can suppress the intrusion of moisture into the inside of the blade. This can suppress corrosion and damage of the blade and a decrease in insulation of the electrical system.

[0047] Specifically, the water contact angle of the surface of the protective layer is preferably 90° or more, may be 95° or more, or may be 100° or more. When the contact angle is in the above range, adhesion of water to the blade can be suppressed. On the other hand, the upper limit of the water contact angle of the surface of the protective layer is not particularly limited, but is, for example, 120° or less. If the contact angle is too high, the adhesion with the adhesive layer and the surface layer described later may be reduced. The water contact angle of the surface of the protective layer is, for example, 90° or more and 120° or less, may be 95° or more and 120° or less, or may be 100° or more and 120° or less.

[0048] The contact angle of water is measured using a contact angle meter by the static drop method in accordance with JIS R3257:1999. Specifically, a 2 μL droplet of pure water is dropped onto the surface of the protective layer of the protective film, and the contact angle of water is measured 1 second after the droplet lands. The atmosphere is set to a temperature of 25°C and a humidity of 50% RH. The contact angle of water is calculated by the θ / 2 method.

[0049] In general, polyolefin resins are hydrophobic and tend to have a high contact angle with water.

[0050] (i) Gel Fraction When the protective layer contains a crosslinked polyolefin resin or a non-crosslinked polyolefin resin as described below, the degree of crosslinking can be represented by the gel fraction.

[0051] When the protective layer contains a non-crosslinked polyolefin resin, the gel fraction of the protective layer is usually 5% or less, and preferably 0%.

[0052] On the other hand, when the protective layer contains a crosslinked polyolefin resin, the gel fraction of the protective layer is, for example, preferably 50% or more, more preferably 60% or more. In this case, the gel fraction of the protective layer is preferably 90% or less, more preferably 80% or less. Specifically, the gel fraction of the protective layer is preferably 50% or more and 90% or less, more preferably 60% or more and 80% or less.

[0053] In this specification, the gel fraction (%) is measured by the following method. First, 1.0 g of the protective layer is placed in a resin mesh and extracted with 110°C xylene for 24 hours. Next, the protective layer is taken out together with the resin mesh, dried, and then weighed. Next, the mass % of the residual insoluble matter is measured by comparing the mass before and after extraction. The mass % of the residual insoluble matter is then defined as the gel fraction.

[0054] The gel fraction of 0% means that the residual insoluble matter is substantially 0 and the crosslinking reaction of the resin composition has not substantially started. More specifically, the gel fraction of 0% means that the residual insoluble matter does not exist at all and that the mass % of the residual insoluble matter measured by a precision balance is less than 0.05 mass %.

[0055] The residual insoluble matter does not include pigment components other than the resin components. When the residual insoluble matter is found to contain impurities other than the resin components in the above test, the gel fraction that should be obtained for the residual insoluble matter derived from the resin components excluding these impurities can be calculated, for example, by separately measuring the contents of these impurities in the resin components in advance.

[0056] (2) Protective layer material (a) Polyolefin resin The polyolefin-based resin may be obtained by polymerizing only olefins, or may be obtained by copolymerizing olefins and monomers other than olefins. That is, the polyolefin-based resin may be composed of only olefins, or may be composed of olefins and monomers other than olefins. Among them, the polyolefin-based resin is preferably composed of only olefins.

[0057] Examples of polyolefin resins include polyethylene resins and polypropylene resins. Among them, polyethylene resins are preferred.

[0058] The polyethylene resin may be a homopolymer of ethylene, a copolymer of ethylene and an α-olefin, or a copolymer of ethylene and a monomer other than an olefin.

[0059] In the copolymer of ethylene and α-olefin, the α-olefin is preferably an α-olefin having 3 to 12 carbon atoms. Specific examples include propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-heptene, 4-methyl-pentene-1, 4-methyl-hexene-1, and 4,4-dimethylpentene-1. The α-olefin may be used alone or in combination of two or more. Among them, unbranched α-olefins are preferred, and unbranched α-olefins having 3 to 8 carbon atoms are more preferred. Specific examples include 1-propene, 1-butene, 1-pentene, 1-hexene, 1-heptene, and 1-octene. The α-olefin having 3 to 8 carbon atoms can impart good flexibility and good strength.

[0060] Specific examples of copolymers of ethylene and α-olefins include ethylene-propylene copolymers, ethylene-1-butene copolymers, ethylene-1-hexene copolymers, ethylene-1-octene copolymers, and ethylene-4-methyl-pentene-1 copolymers.

[0061] A specific example of the copolymer of ethylene and a monomer other than an olefin is an ethylene-vinyl acetate copolymer.

[0062] Examples of polyethylene resins include high density polyethylene (HDPE), low density polyethylene (LDPE), linear low density polyethylene (LLDPE), metallocene linear low density polyethylene (M-LLDPE), and very low density polyethylene (VLDPE). The polyethylene resins may be used alone or in combination of two or more.

[0063] Among them, low density polyethylene (LDPE), linear low density polyethylene (LLDPE), metallocene linear low density polyethylene (M-LLDPE), and very low density polyethylene (VLDPE) are preferred. They have good flexibility, transparency, and processability. Since the protective layer can be given good flexibility, the protective layer of the protective film can absorb the impact caused by collision with the blade, and the occurrence of erosion can be suppressed. In addition, the ability to conform to the curved surface of the blade can be improved.

[0064] Metallocene linear low density polyethylene (M-LLDPE) is synthesized using a metallocene catalyst, which is a single-site catalyst. In such polyethylene resins, there is little branching of the side chains and the distribution of the comonomers is uniform. This allows for a narrow molecular weight distribution and low density, which gives flexibility and strength. In addition, the crystallinity distribution is narrow and the crystal size is uniform, so not only are there no crystals with large sizes, but the low density also means that the crystallinity itself is low. This gives the resin excellent transparency.

[0065] The density of the polyethylene resin is not particularly limited. The density of the polyethylene resin is, for example, 0.950 g / cm 3 Less than or equal to 0.930 g / cm 3 or less, 0.925 g / cm 3 or less, 0.920 g / cm 3or less. When the density of the polyethylene resin is in the above range, flexibility, transparency, and processability can be improved. Since the protective layer can be given good flexibility, the protective layer of the protective film can absorb the impact caused by collision with the blade, and the occurrence of erosion can be suppressed. In addition, the ability to conform to the curved surface of the blade can be improved. In addition, when the density of the polyethylene resin is in the above range, the unit weight of the protective layer can be reduced, and the weight of the protective film can be reduced. On the other hand, the density of the polyethylene resin is, for example, 0.850 g / cm 3 More than 0.870g / cm 3 That is, the density of the polyethylene resin may be, for example, 0.850 g / cm 3 More than 0.950g / cm 3 Less than or equal to 0.850 g / cm 3 More than 0.930g / cm 3 or less, 0.870 g / cm 3 More than 0.925g / cm 3 or less, 0.870 g / cm 3 More than 0.920g / cm 3 It may be the following.

[0066] The density of polyethylene resins is measured by the pycnometer method in accordance with ISO 1183:2019.

[0067] The melting point of the polyethylene resin is not particularly limited. The melting point of the polyethylene resin is, for example, 100°C or less. With polyolefin resins, the lower the melting point, the softer they tend to be. Therefore, if the melting point is within the above range, the protective layer can be given good flexibility, so that the protective layer of the protective film can absorb the impact caused by the collision with the blade, and the occurrence of erosion can be suppressed. In addition, the ability to follow the curved surface of the blade can be improved. On the other hand, the melting point of the polyethylene resin is, for example, 50°C or more, and may be 60°C or more. If the melting point is too low, the heat resistance may be reduced.

[0068] The melting point of the resin is measured by a differential scanning calorimeter (DSC) in accordance with ISO 3146: 2000. If there are two or more melting point peaks, the higher temperature is taken as the melting point.

[0069] The melt mass flow rate (MFR) of the polyethylene resin at a temperature of 190°C is, for example, preferably 1 g / 10 min or more and 30 g / 10 min or less, more preferably 1 g / 10 min or more and 25 g / 10 min or less, and even more preferably 1 g / 10 min or more and 20 g / 10 min or less. By having the MFR of the polyethylene resin be equal to or less than a predetermined value, the strength can be improved. In addition, by having the MFR of the polyethylene resin be within the above range, the film-forming property and flexibility can be improved.

[0070] The melt mass flow rate (MFR) of polyethylene resins is measured in accordance with ISO 1133-1:2011. The measurement conditions are Method A, temperature 190°C, and load 2.16 kg.

[0071] It is preferable that the polyethylene resin does not contain an ester bond, since this allows for excellent hydrolysis resistance to be obtained.

[0072] The polyolefin resin may be a crosslinked polyolefin resin or a non-crosslinked polyolefin resin, and the polyethylene resin may be a crosslinked polyethylene resin or a non-crosslinked polyethylene resin.

[0073] The crosslinked polyolefin resin refers to a crosslinked polyolefin resin, i.e., a polyolefin resin having crosslinked bonds, whereas the non-crosslinked polyolefin resin refers to a non-crosslinked polyolefin resin.

[0074] The cross-linked polyethylene resin refers to a polyethylene resin that is cross-linked, that is, a polyethylene resin having cross-linked bonds, whereas the non-cross-linked polyethylene resin refers to a polyethylene resin that is not cross-linked.

[0075] As a crosslinking method for crosslinking the polyolefin resin, a general crosslinking method can be applied, for example, a crosslinking method using a crosslinking agent, a silane crosslinking method using silanol condensation, and a crosslinking method using ionizing radiation. Among them, a crosslinking method using a crosslinking agent is preferable.

[0076] As the crosslinking agent, a general crosslinking agent can be used, for example, organic peroxides can be mentioned. As the organic peroxides, for example, peroxycarbonates, peroxyketals, and dialkyl peroxides can be mentioned. As the peroxycarbonates, for example, t-amyl-peroxy-2-ethylhexyl carbonate, t-butylperoxy 2-ethylhexyl carbonate can be mentioned. As the peroxyketals, for example, n-butyl 4,4-di(t-butylperoxy)valerate, ethyl 3,3-di(t-butylperoxy)butyrate, and 2,2-di(t-butylperoxy)butane can be mentioned. As the dialkyl peroxides, for example, di-t-butyl peroxide, t-butylcumyl peroxide, dicumyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, and 2,5-dimethyl-2,5-di(t-peroxy)hexyne-3 can be mentioned. The crosslinking agent may be used alone or in combination of two or more kinds.

[0077] In the resin composition used to form the protective layer, the content of the crosslinking agent is appropriately selected depending on the desired degree of crosslinking, etc.

[0078] In addition, in the crosslinking method using a crosslinking agent, a crosslinking assistant may be used. By using the crosslinking assistant, it is possible to promote an appropriate crosslinking reaction. Furthermore, the crosslinking assistant reduces the crystallinity of the polyolefin resin, so that the transparency can be maintained. As the crosslinking assistant, a general crosslinking assistant can be used, and for example, a polyfunctional monomer having a polymerizable functional group can be mentioned.

[0079] Among them, from the viewpoint of improving reactivity, the crosslinking auxiliary is preferably a nurate ring-containing compound having two or more polymerizable functional groups in one molecule.

[0080] In the crosslinking aid, the number of polymerizable functional groups is preferably 2 to 6 in one molecule, more preferably 2 to 3 in one molecule. If the number of polymerizable functional groups is too small, the crosslinking density may not be increased sufficiently. On the other hand, if the number of polymerizable functional groups is too large, the physical properties of the protective layer may be adversely affected, such as the protective layer becoming brittle after crosslinking treatment.

[0081] The polymerizable functional group is not particularly limited as long as it can react with the polyolefin resin, which is the base resin, and can impart a crosslinked structure, but among them, a group having a carbon-carbon double bond, an epoxy group, etc. Examples of the group having a carbon-carbon double bond include a vinyl group, a (meth)acryloyl group, a (meth)acryloyloxy group, and an allyl group.

[0082] Examples of the crosslinking aid include polyallyl compounds, poly(meth)acryloxy compounds, and epoxy compounds. Examples of the polyallyl compounds include triallyl isocyanurate (TAIC), triallyl cyanurate, diallyl phthalate, diallyl fumarate, and diallyl maleate. Examples of the poly(meth)acryloxy compounds include trimethylolpropane trimethacrylate (TMPT), trimethylolpropane triacrylate (TMPTA), ethylene glycol diacrylate, ethylene glycol dimethacrylate, 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate, and 1,9-nonanediol diacrylate. Examples of the epoxy compounds include epoxy compounds containing a double bond and an epoxy group, and epoxy compounds containing two or more epoxy groups. Examples of the epoxy compounds containing a double bond and an epoxy group include glycidyl methacrylate and 4-hydroxybutyl acrylate glycidyl ether. Examples of epoxy compounds containing two or more epoxy groups include 1,6-hexanediol diglycidyl ether, 1,4-butanediol diglycidyl ether, cyclohexanedimethanol diglycidyl ether, and trimethylolpropane polyglycidyl ether. The crosslinking aid may be used alone or in combination of two or more.

[0083] Among them, it is preferable to use triallyl isocyanurate (TAIC) as a crosslinking aid. Triallyl isocyanurate (TAIC) has good compatibility with linear low-density polyethylene, and can reduce crystallinity by crosslinking and maintain transparency. Furthermore, triallyl isocyanurate (TAIC) can impart flexibility at low temperatures to the protective layer.

[0084] In the resin composition used to form the protective layer, the content of the crosslinking aid is appropriately selected depending on the desired degree of crosslinking, etc.

[0085] The content of the polyolefin resin is, for example, preferably 90 parts by mass or more, and more preferably 95 parts by mass or more, relative to 100 parts by mass of all resin components contained in the protective layer, which can improve transparency and flexibility.

[0086] The ratio of each resin component contained in the protective layer is analyzed from the peak ratio detected by differential scanning calorimetry (DSC).

[0087] (b) Additives The protective layer may contain additives as necessary. Examples of additives include light stabilizers, ultraviolet absorbers, antioxidants, heat stabilizers, nucleating agents, dispersants, leveling agents, plasticizers, defoamers, flame retardants, and fillers. Of these, the protective layer preferably contains a weathering agent. Examples of weathering agents include light stabilizers, ultraviolet absorbers, and antioxidants.

[0088] Examples of light stabilizers include hindered amine light stabilizers (HALS). Hindered amine light stabilizers are roughly divided into three types according to the bond partner of the nitrogen atom in the piperidine skeleton: NH type (hydrogen bonded to nitrogen atom), NR type (alkyl group (R) bonded to nitrogen atom), and N-OR type (alkoxy group (OR) bonded to nitrogen atom). Among them, N-OR type hindered amine light stabilizers are preferred. N-OR type has a faster speed of capturing radicals than NH type and NR type. Furthermore, N-OR type low molecular weight HALS, which migrates to the surface faster than polymer HALS, captures radicals in a shorter period of time than NH type and N-CH3 type HALS. Therefore, deterioration of the protective layer can be suppressed.

[0089] The weather resistant agent such as the light stabilizer, the ultraviolet absorber and the antioxidant may be added to the resin composition as a weather resistant master batch dispersed in the resin. The weather resistant master batch may be prepared appropriately or may be a commercially available product. The resin used in the weather resistant master batch may be the polyolefin resin described above or other resins.

[0090] The content of the additive in the protective layer is, for example, 5% by mass or less.

[0091] (3) Layer structure of protective layer The protective layer may have at least a polyolefin resin film containing a polyolefin resin. The protective layer may be a single layer composed of a polyolefin resin film, or may be a multilayer having a polyolefin resin film. When the protective layer has a plurality of polyolefin resin films, the polyolefin resins contained in each polyolefin resin film may be the same or different. In addition, in the case of a multilayer, the protective layer may have a polyolefin resin film and a surface film that is disposed on the surface of the polyolefin resin film opposite to the adhesive layer and contains a cured product of an electron beam curable resin composition.

[0092] (a) Surface film 2, the protective layer 1 may have a polyolefin resin film 1a containing a polyolefin resin, and a surface film 1b containing a cured product of an electron beam curable resin composition and disposed on the surface of the polyolefin resin film 1a opposite to the adhesive layer 2. The durability of the protective layer can be further improved by having the surface film.

[0093] The electron beam curable resin composition contains at least an electron beam curable resin, which may be appropriately selected from a polymerizable monomer, a polymerizable oligomer, and a polymerizable prepolymer.

[0094] The surface film may contain an ultraviolet absorbing agent. As described later, when no primer film is arranged between the polyolefin resin film and the surface film, the surface film preferably contains an ultraviolet absorbing agent. On the other hand, when a primer film is arranged between the polyolefin resin film and the surface film, at least one of the surface film and the primer film preferably contains an ultraviolet absorbing agent.

[0095] The ultraviolet absorbing agent may be either an inorganic ultraviolet absorbing agent or an organic ultraviolet absorbing agent.

[0096] As the inorganic ultraviolet absorbing agent, for example, titanium oxide, cerium oxide, and zinc oxide having an average particle size of about 5 nm or more and 120 nm or less are preferable.

[0097] Examples of organic ultraviolet absorbers include benzotriazole ultraviolet absorbers, triazine ultraviolet absorbers, benzophenone ultraviolet absorbers, salicylate ultraviolet absorbers, and acrylonitrile ultraviolet absorbers. Examples of benzotriazole ultraviolet absorbers include 2-(2-hydroxy-5-methylphenyl)benzotriazole, 2-(2-hydroxy-3,5-di-tert-amylphenyl)benzotriazole, and 3-[3-(benzotriazol-2-yl)-5-tert-butyl-4-hydroxyphenyl]propionic acid ester of polyethylene glycol. Examples of triazine-based ultraviolet absorbers include 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-[(hexyl)oxy]phenol, 1,3,5-triazine-2,4,6(1H,3H,5H)-trione, and 1,3,5-tri[[3,5-bis-(1,1-dimethylethyl)-4-hydroxyphenyl]methyl].

[0098] The surface film may contain additives other than the ultraviolet absorber, if necessary.

[0099] In order to impart weather resistance to the surface film, a light stabilizer may be used in combination with the ultraviolet absorber. Examples of light stabilizers include hindered amine light stabilizers. Specific examples include 2-(3,5-di-tert-butyl-4-hydroxybenzyl)-2'-n-butylmalonic acid bis(1,2,2,6,6-pentamethyl-4-piperidyl), bis(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate, and tetrakis(2,2,6,6-tetramethyl-4-piperidyl)-1,2,3,4-butanetetracarboxylate.

[0100] Examples of other additives include abrasion resistance improvers, polymerization inhibitors, crosslinking agents, infrared absorbing agents, antistatic agents, adhesion improvers, leveling agents, thixotropy imparting agents, coupling agents, plasticizers, defoamers, fillers, solvents, and colorants.

[0101] (b) Primer film The protective layer may have a primer film between the polyolefin resin film and the surface film, which can improve the adhesion between the polyolefin resin film and the surface film.

[0102] (4) Thickness of the protective layer The thickness of the protective layer is not particularly limited as long as a protective layer satisfying the above-mentioned physical properties can be obtained. The thickness of the protective layer is, for example, 50 μm or more, may be 80 μm or more, or may be 100 μm or more. If the thickness of the protective layer is within the above range, sufficient erosion resistance can be obtained. On the other hand, the thickness of the protective layer is, for example, 1000 μm or less, may be 700 μm or less, or may be 500 μm or less. By having the thickness of the protective layer within the above range, the protective film can be easily stretched, and the adhesion and followability to uneven and curved surfaces can be improved. In addition, if the thickness of the protective layer is within the above range, sufficient transparency can be ensured. Specifically, the thickness of the protective layer is 50 μm or more and 1000 μm or less, may be 80 μm or more and 700 μm or less, or may be 100 μm or more and 500 μm or less.

[0103] When the protective layer is a multi-layered layer, the thickness of the protective layer is the thickness of the entire protective layer.

[0104] (5) Method for forming protective layer The protective layer can be obtained, for example, by mixing the above-mentioned components to prepare a resin composition, melting the resin composition, and forming the resin composition into a sheet-like film. After the film formation, a crosslinking treatment may be performed.

[0105] As a method for mixing each component, for example, a method of impregnating each component into a polyolefin resin by dry blending can be mentioned. In addition, when the protective layer is obtained by extrusion molding, the crosslinking agent and crosslinking aid may be added in a liquid state to the polyolefin resin. In addition, the crosslinking aid may be kneaded in advance with the polyolefin resin, and the mixture may be made into a master batch. When a master batch is used, the dispersibility of the crosslinking aid is improved.

[0106] The melt molding method may be any general molding method, such as injection molding, extrusion molding, blow molding, compression molding, and rotational molding. The molding temperature may be a temperature that exceeds the melting point of the resin composition. The molding temperature may be a temperature at which crosslinking does not start during film formation, that is, a temperature at which the gel fraction of the resin composition can be maintained at 0%, depending on the crosslinking agent. The molding temperature is, for example, 80°C or higher and 250°C or lower.

[0107] As described above, examples of the crosslinking treatment include a crosslinking treatment using a crosslinking agent and a crosslinking treatment by irradiation with ionizing radiation.

[0108] The surface of the protective layer on the adhesive layer side may be subjected to an easy-adhesion treatment if necessary. This can improve the adhesion to the adhesive layer. In addition, when the protective layer is multi-layered, the surface of the polyolefin resin film opposite to the adhesive layer may be subjected to an easy-adhesion treatment if necessary. This can improve the adhesion between the polyolefin resin film and the surface film or primer film. Examples of the easy-adhesion treatment include corona discharge treatment, plasma treatment, and ozone treatment.

[0109] 2.Adhesive layer The adhesive layer in the present disclosure is a member for attaching the protective film to the blades of a wind turbine generator.

[0110] The adhesive layer is not particularly limited as long as it can attach the protective film to the blade, and is appropriately selected according to the material of the blade. A general adhesive can be used for the adhesive layer. For example, an ultraviolet curing adhesive, a two-component curing adhesive, and a pressure-sensitive adhesive can be mentioned. The ultraviolet curing adhesive and the two-component curing adhesive can increase the adhesive strength. In addition, the pressure-sensitive adhesive has good workability.

[0111] Examples of pressure-sensitive adhesives include acrylic adhesives, urethane adhesives, and silicone adhesives. Among them, acrylic adhesives are preferred. Acrylic adhesives are excellent in transparency, weather resistance, heat resistance, and the like.

[0112] The thickness of the adhesive layer is not particularly limited as long as it can bond the protective film and the blade, and is appropriately selected according to the application. The thickness of the adhesive layer is, for example, 25 μm or more, may be 25 μm or more, or may be 30 μm or more. The thickness of the adhesive layer is, for example, 120 μm or less, may be 90 μm or less, or may be 80 μm or less. That is, the thickness of the adhesive layer is, for example, 25 μm or more and 120 μm or less, may be 25 μm or more and 90 μm or less, or may be 30 μm or more and 80 μm or less.

[0113] 3. Other configurations The protective film of the present disclosure may have other configurations depending on the application.

[0114] The protective film in the present disclosure may have a separator on the surface of the adhesive layer opposite the protective layer.

[0115] 4.Properties of protective film (1) Adhesive strength In the protective film of the present disclosure, the adhesive strength to the SUS plate is, for example, preferably 3N / 10mm or more, may be 7N / 10mm or more, or may be 10N / 10mm or more. When the adhesive strength is in the above range, durability can be improved. On the other hand, the upper limit of the adhesive strength to the SUS plate is not particularly limited, but is, for example, preferably 30N / 10mm or less, may be 25N / 10mm or less, or may be 20N / 10mm or less. If the adhesive strength is too large, the workability when replacing the protective film may be deteriorated. Specifically, the adhesive strength to the SUS plate is preferably 3N / 10mm or more and 30N / 10mm or less, may be 7N / 10mm or more and 25N / 10mm or less, or may be 10N / 10mm or more and 20N / 10mm or less.

[0116] The adhesive strength to the SUS plate is measured in accordance with JIS Z0237:2009, Method 6. The specific measurement conditions are shown below. For example, the tensile tester used is "Tensilon RTF1150" manufactured by A&D Co., Ltd. The SUS plate used is a steel plate of SUS304 with a surface finish of BA.

[0117] <Measurement conditions> Tape width: 10mm Peeling speed: 300mm / min Peel angle: 90 degrees Test conditions: 23℃, 50% RH Number of tests: Measurements are performed on three test pieces, and the arithmetic average value is used.

[0118] In the protective film of the present disclosure, the adhesive strength to the fluororesin layer is, for example, preferably 2.5 N / 10 mm or more, may be 4 N / 10 mm or more, or may be 5 N / 10 mm or more. The adhesive strength in the above range can improve durability. On the other hand, the upper limit of the adhesive strength to the fluororesin layer is not particularly limited, but is, for example, preferably 30 N / 10 mm or less, may be 25 N / 10 mm or less, or may be 20 N / 10 mm or less. If the adhesive strength is too large, the workability at the time of replacing the protective film may be deteriorated. Specifically, the adhesive strength to the fluororesin layer is preferably 2.5 N / 10 mm or more and 30 N / 10 mm or less, may be 4 N / 10 mm or more and 25 N / 10 mm or less, or may be 5 N / 10 mm or more and 20 N / 10 mm or less.

[0119] The adhesive strength to the fluororesin layer is measured in accordance with Method 6 of JIS Z0237:2009. The specific measurement conditions are the same as those for measuring the adhesive strength to the SUS plate. For example, a tensile tester such as "Tensilon RTF1150" manufactured by A&D Co., Ltd. is used. Instead of the SUS plate, a test plate prepared by the following method is used. A fluororesin paint ("Wind Hullo Topcoat F" manufactured by Nippon Tokushu Toryo Co., Ltd.) is applied to one side of the SUS substrate by the roller method to form a fluororesin layer with a thickness of 100 μm to 150 μm, which is used as the test plate.

[0120] In addition, in the protective film of the present disclosure, the adhesive strength (N / 10 mm) to the fluororesin layer is preferably equal to or greater than the tensile load (N) at 10% elongation of the protective layer, thereby improving durability.

[0121] The tensile load of the protective layer at 10% elongation is measured using a tensile tester in accordance with ISO 527-3:2018. The measurement conditions are the same as those for the tensile modulus measurement described above. For example, the tensile tester used is "Tensilon RTF1150" manufactured by A&D Co., Ltd.

[0122] (2) Total light transmittance In the present disclosure, the total light transmittance of the protective film is, for example, preferably 60% or more, more preferably 65% ​​or more, and even more preferably 70% or more. If the total light transmittance is within the above range, the transparency is good. Therefore, the surface of the blade can be visually confirmed through the protective film, and it is easy to determine when to replace the protective film. The total light transmittance is measured in accordance with ISO 13468-1:1996.

[0123] (3) Erosion depth In the present disclosure, the erosion depth from the surface of the protective film on the protective layer side when the amount of projected particles is 40 g, obtained by a microslurry jet erosion (MSE) test, is, for example, preferably 10 μm or less, may be 8 μm or less, or may be 5 μm or less. If the erosion depth is within the above range, durability can be improved. The lower limit of the erosion depth is not particularly limited.

[0124] The erosion depth is a value obtained by a micro-slurry jet erosion (MSE) test. In the MSE test, a certain amount of particles is projected onto the same point on the sample surface, and the erosion depth is measured repeatedly to obtain the relationship between the amount of projected particles and the erosion depth.

[0125] The erosion depth is measured using the MSE tester "MSE-A" manufactured by Palmeso. The measurement conditions are as follows. The surface of the protective film facing the protective layer is used as the sample surface, and measurements are taken at three points, and the arithmetic average value is used.

[0126] <Measurement conditions> Particles: Polygonal alumina (average particle size 1.2 μm) ·Projection particle speed: 360km / hour Test conditions: 25℃, 50% RH

[0127] (4) Thickness uniformity In the present disclosure, the thickness of the protective film is preferably uniform. If the protective film has a portion with an extremely thin thickness, the protective film may stretch from that portion, which may cause a difference in durability within the protective film surface. Specifically, when the maximum thickness of the protective film is taken as 100%, the minimum thickness of the protective film is preferably 80% or more, more preferably 90% or more.

[0128] The thickness of the protective film is measured using a contact thickness gauge in accordance with JIS K7130:1999. The thickness of the protective film is measured at multiple points in both the vertical and horizontal directions. For example, for a protective film that is 30 cm long and 20 cm wide, the thickness of the protective film is measured at 10 points at 3 cm intervals in the vertical direction and at 10 points at 2 cm intervals in the horizontal direction. For example, a Mitutoyo ID-C112X is used as the contact thickness gauge.

[0129] 5.Applications The protective film in the present disclosure is attached to the surface of the blade of a wind turbine generator. For example, as shown in Fig. 3(a) and Fig. 3(b), the protective film 10 is disposed on the tip 22 of the leading edge 21 of the blade 20.

[0130] B. Wind turbine blades The blades of the wind turbine power generation device in the present disclosure have the above-mentioned protective film on their surfaces.

[0131] Fig. 3(a) is a schematic perspective view showing an example of a blade in the present disclosure, and Fig. 3(b) is a cross-sectional view taken along line AA in Fig. 3(a). As shown in Fig. 3(a) and Fig. 3(b), a blade 20 has a protective film 10 on its surface. In Fig. 3(a) and Fig. 3(b), the protective film 10 is disposed on a tip 22 of a leading edge 21 of the blade 20.

[0132] In the present disclosure, the occurrence of erosion can be suppressed by having the above-mentioned protective film.

[0133] The protective film is preferably disposed on the leading edge of the blade, and more preferably on the tip of the leading edge of the blade, because erosion mainly occurs at the tip of the leading edge.

[0134] The structure and materials of the blade are the same as those of a general blade, so a description thereof will be omitted here.

[0135] C. Wind power generation equipment The wind turbine generator of the present disclosure includes the blade described above.

[0136] Fig. 4 is a schematic diagram showing an example of a wind power generation device in the present disclosure. As shown in Fig. 4, the wind power generation device 30 includes a rotor 32 having a blade 20 and a hub 31 supporting the blade 20, a nacelle 33, and a tower 34 supporting the rotor 32 and the nacelle 33. Although not shown, the nacelle 33 houses a main shaft connected to the hub 31 and rotating together with the hub 31, a speed increaser connected to the main shaft for increasing the rotation speed, and a generator that rotates the rotor at the rotation speed increased by the speed increaser to generate electricity. In Fig. 4, a protective film 10 is disposed on the tip of the leading edge of the blade 20.

[0137] In the present disclosure, by having the above-mentioned blade, the occurrence of erosion in the blade can be suppressed.

[0138] The components constituting the wind turbine generator are similar to those of a typical wind turbine generator, and therefore a description thereof will be omitted here.

[0139] The present disclosure is not limited to the above-described embodiments. The above-described embodiments are merely examples, and anything that has substantially the same configuration as the technical idea described in the claims of the present disclosure and exhibits similar effects is included in the technical scope of the present disclosure. EXAMPLES

[0140] The present disclosure will be described in further detail below with reference to examples and comparative examples.

[0141] [Manufacturing Example A1] The following base resin and weather resistant masterbatch were used: Base resin: Density 0.901g / cm 3 A metallocene-based linear low-density polyethylene resin (M-LLDPE) with a melting point of 93°C and an MFR of 2.0g / 10min at 190°C. Weatherproofing masterbatch: density is 0.880g / cm 3 100 parts by mass of a low-density polyethylene resin having an MFR of 3.5 g / 10 min at 190° C. was mixed with 0.6 parts by mass of HALS1 ("KEMISTAB62" manufactured by Chemipro Chemical Co., Ltd.), 3.5 parts by mass of ultraviolet absorber 1 ("KEMISORB12" manufactured by Chemipro Chemical Co., Ltd.), and 0.6 parts by mass of ultraviolet absorber 2 ("KEMISORB79" manufactured by Chemipro Chemical Co., Ltd.).

[0142] The above weathering agent master batch was mixed at a ratio of 5 parts by mass to 95 parts by mass of the above base resin to prepare a resin composition. The above resin composition was formed into a sheet at an extrusion temperature of 210°C using a film forming machine having a φ30 mm extruder and a 200 mm wide T-die to form a protective layer with a thickness of 300 μm. The take-up speed was adjusted to a predetermined thickness. In addition, for the cooling roll and rubber roll immediately below the T-die, the cooling roll was a chrome-plated cooling roll with a surface roughness of Rz1.5 μm, and the rubber roll was a silicone rubber roll with a hardness of 70 degrees.

[0143] [Manufacturing example A2] A protective layer was formed in the same manner as in Production Example A1, except that the following base resin and weather resistance agent masterbatch were used. Base resin: Density 0.87g / cm 3 A low-density polyethylene resin (LDPE) with a melting point of 55°C and a MFR of 3.6g / 10min at 190°C. Weatherproofing masterbatch: density is 0.880g / cm 3100 parts by mass of a low-density polyethylene resin having an MFR of 3.5 g / 10 min at 190° C. was mixed with 0.6 parts by mass of HALS ("KEMISTAB62" manufactured by Chemipro Chemical Co., Ltd.), 3.5 parts by mass of ultraviolet absorber 1 ("KEMISORB12" manufactured by Chemipro Chemical Co., Ltd.), and 0.6 parts by mass of ultraviolet absorber 2 ("KEMISORB79" manufactured by Chemipro Chemical Co., Ltd.).

[0144] [Manufacturing example A3] A protective layer was formed in the same manner as in Production Example A1, except that the following base resin and weather resistance agent masterbatch were used. Base resin: Density 0.88g / cm 3 A metallocene-based linear low-density polyethylene resin (M-LLDPE) with a melting point of 60°C and an MFR of 3.5g / 10min at 190°C. Weatherproofing masterbatch: density is 0.880g / cm 3 100 parts by mass of a low-density polyethylene resin having an MFR of 3.5 g / 10 min at 190° C. was mixed with 0.6 parts by mass of HALS ("KEMISTAB62" manufactured by Chemipro Chemical Co., Ltd.), 3.5 parts by mass of ultraviolet absorber 1 ("KEMISORB12" manufactured by Chemipro Chemical Co., Ltd.), and 0.6 parts by mass of ultraviolet absorber 2 ("KEMISORB79" manufactured by Chemipro Chemical Co., Ltd.).

[0145] [Manufacturing example A4] A protective layer was formed in the same manner as in Production Example A1, except that the following base resin and weather resistance agent masterbatch were used. Base resin: Density 0.960g / cm 3 Ethylene-vinyl acetate copolymer resin (EVA) with a melting point of 61°C and a MFR of 30g / 10min at 190°C Weatherproofing masterbatch: density is 0.960g / cm 3 100 parts by mass of an ethylene-vinyl acetate copolymer resin having a melting point of 61°C and an MFR at 190°C of 30 g / 10 min was mixed with 0.6 parts by mass of HALS ("KEMISTAB62" manufactured by Chemipro Chemical Co., Ltd.), 3.5 parts by mass of ultraviolet absorber 1 ("KEMISORB12" manufactured by Chemipro Chemical Co., Ltd.), and 0.6 parts by mass of ultraviolet absorber 2 ("KEMISORB79" manufactured by Chemipro Chemical Co., Ltd.).

[0146] [Manufacturing example A5] The following base resin and weather resistant masterbatch were used: Base resin 1: Density 0.87g / cm 3 A low-density polyethylene resin (LDPE) with a melting point of 55°C and a MFR of 1.2g / 10min at 190°C. Base resin 2: Density 0.901g / cm 3 A metallocene-based linear low-density polyethylene resin (M-LLDPE) with a melting point of 93°C and an MFR of 2.0g / 10min at 190°C. Weatherproofing masterbatch: density is 0.880g / cm 3 100 parts by mass of a low-density polyethylene resin having an MFR of 3.5 g / 10 min at 190° C. was mixed with 0.6 parts by mass of HALS ("KEMISTAB62" manufactured by Chemipro Chemical Co., Ltd.), 3.5 parts by mass of ultraviolet absorber 1 ("KEMISORB12" manufactured by Chemipro Chemical Co., Ltd.), and 0.6 parts by mass of ultraviolet absorber 2 ("KEMISORB79" manufactured by Chemipro Chemical Co., Ltd.).

[0147] Resin composition 1 was prepared by mixing 95 parts by mass of the base resin 1 with 5 parts by mass of the weathering agent master batch. Resin composition 2 was prepared by mixing 95 parts by mass of the base resin 2 with 5 parts by mass of the weathering agent master batch. Using a film molding machine having a φ30 mm extruder and a 200 mm wide T-die, the resin compositions 1 and 2 were formed into a sheet at an extrusion temperature of 210° C. in the order of resin composition 1, resin composition 2, and resin composition 1 to form a three-layer structure, and the thicknesses of the layers were 30 μm, 260 μm, and 30 μm, forming a protective layer with a total thickness of 300 μm. The take-up speed was adjusted to a predetermined thickness. In addition, for the cooling roll and rubber roll immediately below the T-die, a chrome-plated cooling roll with a surface roughness Rz of 1.5 μm was used as the cooling roll, and a silicone rubber roll with a hardness of 70 degrees was used as the rubber roll.

[0148] [Manufacturing example B1] A pre-solution was prepared by mixing and stirring 70g of water-dispersible polycarbonate polyurethane A (cyclohexane skeleton content: about 36% by mass), 0.85g of UV absorber 3 (BASF Japan "Tinuvin 1130"), 0.5g of HALS2 (BASF Japan "Tinuvin 292"), 0.2g of TritonGR-7M (Dow Chemical Company, surfactant), 0.1g of neutralizer (ANGUS Chemical Company "AMP95"), and 3g of deionized water. The pre-solution was bar-coated on a PET film, dried at 90°C for 3 minutes in a hot air oven, and further dried and cured at 160°C for 3 minutes. This formed a protective layer with a thickness of 300 μm.

[0149] [Manufacturing example B2] A protective layer was formed in the same manner as in Production Example A1, except that the following base resin and weather resistance agent masterbatch were used. Base resin: Density 1.15g / cm 3 A urethane resin having a glass transition temperature of -25°C. Weather resistance master batch: 100 parts by mass of the above urethane resin were mixed with 0.6 parts by mass of HALS ("KEMISTAB62" manufactured by Chemipro Chemical Co., Ltd.), 3.5 parts by mass of UV absorber 1 ("KEMISORB12" manufactured by Chemipro Chemical Co., Ltd.), and 0.6 parts by mass of UV absorber 2 ("KEMISORB79" manufactured by Chemipro Chemical Co., Ltd.).

[0150] [Manufacturing Example B3] The following base resin and weather resistant masterbatch were used: Base resin: Density 0.93g / cm 3 High density polyethylene resin (HDPE) with a melting point of 130°C or less and a MFR of 1.5g / 10min at 190°C Weatherproofing masterbatch: density is 0.880g / cm 3 100 parts by mass of a low-density polyethylene resin having an MFR of 3.5 g / 10 min at 190° C. was mixed with 0.6 parts by mass of HALS ("KEMISTAB62" manufactured by Chemipro Chemical Co., Ltd.), 3.5 parts by mass of ultraviolet absorber 1 ("KEMISORB12" manufactured by Chemipro Chemical Co., Ltd.), and 0.6 parts by mass of ultraviolet absorber 2 ("KEMISORB79" manufactured by Chemipro Chemical Co., Ltd.).

[0151] A resin composition was prepared by mixing 95 parts by mass of the base resin with 5 parts by mass of the weathering agent master batch. Using a film molding machine having a φ30 mm extruder and a 200 mm wide T-die, the resin composition was formed into a sheet at an extrusion temperature of 210°C to form a protective layer with a thickness of 300 μm. The take-up speed was adjusted to obtain a predetermined thickness. Regarding the cooling roll and rubber roll immediately below the T-die, the cooling roll was a chrome-plated cooling roll with a surface roughness of Rz 1.5 μm, and the rubber roll was a silicone rubber roll with a hardness of 70 degrees.

[0152] [Manufacturing example B4] A protective layer was formed in the same manner as in Production Example B3, except that the following base resin and weather resistance agent masterbatch were used. Base resin: Density 0.864g / cm 3 Low-density polyethylene resin (LDPE) with a melting point of 50°C or less and a MFR of 3.6g / 10min at 190°C Weatherproofing masterbatch: density is 0.880g / cm 3 100 parts by mass of a low-density polyethylene resin having an MFR of 3.5 g / 10 min at 190° C. was mixed with 0.6 parts by mass of HALS ("KEMISTAB62" manufactured by Chemipro Chemical Co., Ltd.), 3.5 parts by mass of ultraviolet absorber 1 ("KEMISORB12" manufactured by Chemipro Chemical Co., Ltd.), and 0.6 parts by mass of ultraviolet absorber 2 ("KEMISORB79" manufactured by Chemipro Chemical Co., Ltd.).

[0153] [Rating 1] (1) Tensile modulus The tensile modulus of the protective layer was determined by the method described above in "A. Protective film for wind power generation device blades 1. Protective layer (1) Physical properties of the protective layer (a) Tensile modulus of elasticity." The tensile tester used was "Tensilon RTF1150" manufactured by A&D Co., Ltd.

[0154] (2) Tensile breaking stress The tensile breaking stress of the protective layer was measured by the method described above in "A. Protective film for wind power generation device blades 1. Protective layer (1) Physical properties of the protective layer (b) Tensile breaking stress." The tensile tester used was "Tensilon RTF1150" manufactured by A&D Co., Ltd.

[0155] (3) Tensile elongation at break The tensile breaking elongation of the protective layer was determined by the method described in "A. Protective film for wind power generation device blades 1. Protective layer (1) Physical properties of the protective layer (c) Tensile breaking elongation" above. The tensile tester used was "Tensilon RTF1150" manufactured by A&D Co., Ltd.

[0156] (4) Type A durometer hardness The type A durometer hardness of the protective layer was measured by the method described in "A. Protective film for wind power generation device blades 1. Protective layer (1) Physical properties of the protective layer (d) Type A durometer hardness" above. The hardness meter used was "GS-610" manufactured by TECLOCK.

[0157] (5) Unit weight The unit weight of the protective layer was determined by the method described in "A. Protective film for blades of wind power generation device 1. Protective layer (1) Physical properties of the protective layer (e) Unit weight" above.

[0158] (6) Water vapor permeability The water vapor permeability of the protective layer was measured by the method described above in "A. Protective film for wind turbine blades: 1. Protective layer (1) Physical properties of protective layer (f) Water vapor permeability."

[0159] (7) Water contact angle The water contact angle of the surface of the protective layer was measured by the method described above in "A. Protective film for wind power generation device blades 1. Protective layer (1) Physical properties of the protective layer (h) Water contact angle." The contact angle meter used was a contact angle measuring instrument "Drop Master-700" manufactured by Kyowa Interface Science Co., Ltd.

[0160] (8) Total light transmittance The total light transmittance of the protective layer was determined using a haze meter "HM-150" manufactured by Murakami Color Research Laboratory Co., Ltd., according to the method described above in "A. Protective film for wind power generation device blades 1. Protective layer (1) Physical properties of the protective layer (g) Total light transmittance." At this time, the protective layer formed by changing the thickness from 300 μm to 600 μm and 900 μm was also measured.

[0161] (9) Tracking Ability The following components were mixed to prepare a pressure-sensitive adhesive composition. <Adhesive composition> Adhesive: (meth)acrylic acid alkyl ester copolymer (Nissetsu KP-2826 manufactured by Nippon Carbide Industries Co., Ltd., solid content concentration: 30% by mass, solvent: methyl ethyl ketone, ethyl acetate) 100 parts by mass Crosslinking agent: 0.3 parts by mass of chelating compound (Nissetsu CK-401 manufactured by Nippon Carbide Industries Co., Ltd., solid content concentration: 5% by mass, solvent: toluene) Silane coupling agent ("KBM-403" manufactured by Shin-Etsu Chemical Co., Ltd., solid content concentration: 100% by mass) 0.15 parts by mass Phenol-based antioxidant: ADEKA Corporation "Adeka STAB AO-60G", solid content concentration: 100% by mass, 0.38 parts by mass UV absorber: ADEKA "Adeka STAB LA-24", solid content: 100% by mass, 0.38 parts by mass

[0162] Next, the above-mentioned pressure-sensitive adhesive composition was applied to a release-treated surface of a 50 μm-thick PET separator (Nippa Corporation's "PET50x1-J2") so that the thickness after drying was 65 μm, and then dried to form an adhesive layer. After that, the separator and adhesive layer laminate was laminated on one side of the protective layer of each manufacturing example to obtain a protective film.

[0163] The adherend used was a U-shaped handle made of polyamide, 20 mm in diameter, 56 mm in height, and 148 mm in length. The protective film was cut to a width of 20 mm and a length of 100 mm. The protective film was attached to the rounded part of the adherend, and the appearance after 24 hours was visually confirmed. The conformability was evaluated according to the following criteria. A: There was no lifting or peeling. B: Lifting or peeling occurred in less than 10% of the application area. C: Lifting or peeling occurred over 10% or more of the application area.

[0164] (10) Erosion depth A protective film was prepared as described in (9) above. The erosion depth from the protective layer side of the protective film when the amount of projected particles was 40 g was obtained by a microslurry jet erosion (MSE) test using the method described in "A. Protective film for wind power generation device blades 4. Physical properties of the protective film (3) Erosion depth" above.

[0165] (11) Durability test The protective layer or protective film was subjected to the following durability test using "EYE SUPER UV TESTER / SUV-W261" manufactured by Iwasaki Electric Co., Ltd. <Durability test conditions> ·UV irradiation conditions Light source: Metal halide lamp Illuminance: 96mW / cm 2 (Wavelength 300nm to 400nm) Black panel temperature: 63℃ Humidity: 50%RH Duration: 20 hours Condensation conditions (without irradiation) Humidity: 98%RH Duration: 4 hours ·cycle 1 cycle: 20 hours of UV irradiation, 4 hours of condensation Number of cycles: 15 cycles Accumulated exposure time: 300 hours

[0166] The tensile stress at break of the protective layer after the durability test was measured, and the tensile stress at break retention rate was calculated. Similarly, the tensile elongation at break of the protective layer after the durability test was calculated, and the tensile elongation at break retention rate was calculated. In addition, the erosion depth before and after the durability test was calculated, and the erosion depth retention rate before and after the durability test was calculated. The erosion depth retention rate was based on the thickness of the protective layer at the time of film formation.

[0167] [Table 1]

[0168] [Table 2]

[0169] [Table 3]

[0170] [Table 4]

[0171] In Production Examples A1 to A5, the protective layer contained an olefin resin, and the tensile modulus of the protective layer was within a predetermined range, so the durability was good. On the other hand, in Production Examples B1 and B2, the protective layer contained a polyurethane resin, so the durability was poor. In Production Example B3, although the protective layer contained an olefin resin, the tensile modulus of the protective layer was large, so the conformability to a curved surface was poor. In Production Example B4, although the protective layer contained an olefin resin, the tensile modulus of the protective layer was small, so the erosion resistance was poor.

[0172] [Example 1] First, a protective layer was formed in the same manner as in Production Example A1.

[0173] The following components were mixed to prepare a pressure-sensitive adhesive composition. <Adhesive composition> Adhesive: (meth)acrylic acid alkyl ester copolymer (Nissetsu KP-2826 manufactured by Nippon Carbide Industries Co., Ltd., solid content concentration: 30% by mass, solvent: methyl ethyl ketone, ethyl acetate) 100 parts by mass Crosslinking agent: 0.3 parts by mass of chelating compound (Nissetsu CK-401 manufactured by Nippon Carbide Industries Co., Ltd., solid content concentration: 5% by mass, solvent: toluene) Silane coupling agent ("KBM-403" manufactured by Shin-Etsu Chemical Co., Ltd., solid content concentration: 100% by mass) 0.15 parts by mass Phenol-based antioxidant (ADEKA "ADEKA STAB AO-60G", solid content: 100% by mass) 0.38 parts by mass UV absorber (ADEKA "ADEKA STAB LA-24", solid content: 100% by mass) 0.38 parts by mass

[0174] Next, the pressure-sensitive adhesive composition was applied to a release-treated surface of a 50 μm-thick PET separator (Nippa Corporation's "PET50x1-J2") so that the thickness after drying was 65 μm, and then dried to form an adhesive layer. After that, the separator and adhesive layer laminate was laminated on one side of the protective layer to obtain a protective film.

[0175] [Example 2] First, a protective layer was formed in the same manner as in Production Example A1.

[0176] The following components were mixed to prepare a pressure-sensitive adhesive composition. <Adhesive composition> Adhesive: (meth)acrylic acid alkyl ester copolymer (Nissetsu KP-2610 manufactured by Nippon Carbide Industries Co., Ltd., solid content concentration: 45% by mass, solvent: methyl ethyl ketone, ethyl acetate) 100 parts by mass Crosslinking agent: isocyanate-terminated urethane resin (Nissetsu CK-121, manufactured by Nippon Carbide Industries Co., Ltd., solid content concentration: 10% by mass, solvent: methyl ethyl ketone) 0.2 parts by mass Silane coupling agent ("KBM-403" manufactured by Shin-Etsu Chemical Co., Ltd., solid content concentration: 100% by mass) 0.23 parts by mass Phenol-based antioxidant (ADEKA "ADEKA STAB AO-60G", solid content: 100% by mass) 0.57 parts by mass UV absorber (ADEKA "ADEKA STAB LA-24", solid content: 100% by mass) 0.57 parts by mass

[0177] Next, the pressure-sensitive adhesive composition was applied to a release-treated surface of a 50 μm-thick PET separator ("PET50x1-J2" manufactured by Nippa Corporation) so that the thickness after drying was 65 μm, and then dried to form an adhesive layer. After that, the laminate of the separator and the adhesive layer was laminated on one side of the protective layer and aged at 50° C. for 3 days. This resulted in a protective film.

[0178] [Example 3] First, a protective layer was formed in the same manner as in Production Example A2. Next, a protective film was obtained in the same manner as in Example 1.

[0179] [Example 4] First, a protective layer was formed in the same manner as in Production Example A2. Next, a protective film was obtained in the same manner as in Example 2.

[0180] [Example 5] First, a protective layer was formed in the same manner as in Production Example A3. Next, a protective film was obtained in the same manner as in Example 1.

[0181] [Comparative Example 1] First, a protective layer was produced in the same manner as in Production Example B3. Next, a protective film was obtained in the same manner as in Example 1.

[0182] [Comparative Example 2] First, a protective layer was produced in the same manner as in Production Example B3. Next, a protective film was obtained in the same manner as in Example 2.

[0183] [Example 6] First, a protective layer was formed in the same manner as in Production Example A3. Next, a protective film was obtained in the same manner as in Example 2.

[0184] [Rating 2] (1) Adhesion to SUS plate The adhesive strength of the protective film to the SUS plate was measured by the method described above in "A. Protective film for wind power generator blades 4. Physical properties of the protective film (1) Adhesive strength".

[0185] (2) Adhesion to fluororesin layer The adhesive strength of the protective film to the fluororesin layer was measured by the method described above in "A. Protective film for wind turbine blades 4. Physical properties of the protective film (1) Adhesive strength".

[0186] (3) Tensile load at 10% elongation The tensile load at 10% elongation of the protective layer was measured by the method described above in "A. Protective film for wind turbine blades 4. Physical properties of protective film (1) Adhesive strength".

[0187] (4) Lifting and peeling at 10% elongation A test plate used to measure the adhesive strength to the fluororesin layer was prepared. The protective film was cut to a width of 10 mm and a length of 50 mm. The protective film was attached to the fluororesin layer side of the test plate while being stretched by 10% in the length direction, and was stored at 25°C and 50% RH for 24 hours. The state of the protective film was then visually observed. Lifting and peeling were evaluated according to the following criteria. A: No lifting or peeling B: Lifting or peeling

[0188] [Table 5]

[0189] From Table 5, it can be seen that when the adhesive strength of the protective film to the fluororesin layer is equal to or greater than the tensile load at 10% elongation of the protective layer, there is no lifting or peeling at 10% elongation and the durability is excellent.

[0190] [Examples 7 to 9] A protective film was produced in the same manner as in Example 1. In this case, in forming the protective layer, the speed of the take-up roll during film formation was changed in order to adjust the thickness uniformity of the protective layer. By increasing the speed of the take-up roll, a thinner portion was obtained.

[0191] [Rating 3] (1) Thickness uniformity The thickness of the protective film was measured by the method described above in "A. Protective film for wind power generation device blades 4. Physical properties of the protective film (4) Thickness uniformity." In this case, the size of the protective film was 30 cm in length and 20 cm in width, and the thickness of the protective film was measured at 10 points at 3 cm intervals in the vertical direction and at 10 points at 2 cm intervals in the horizontal direction. Next, the minimum value of the thickness of the protective film was determined when the maximum value of the thickness of the protective film was set to 100%.

[0192] (2) Durability test The protective film was subjected to a durability test in the same manner as in (11) Durability test of Evaluation 1 above, and the state of the protective film after the durability test was visually observed. The state of the protective film was evaluated according to the following criteria. A: No change from the initial state B: Compared to the initial state, there are changes such as cracks.

[0193] [Table 6]

[0194] From Table 6, it can be seen that the better the thickness uniformity of the protective film, the better the durability.

[0195] The present disclosure provides the following inventions. [1] A protective layer containing a polyolefin resin and an adhesive layer disposed on one surface of the protective layer, A protective film for blades of a wind turbine generator, wherein the protective layer has a tensile modulus of elasticity of 5 MPa or more and 35 MPa or less. [2] The protective film for blades according to [1], wherein the protective layer has a tensile breaking stress of 5 MPa or more. [3] The protective film for blades according to [1] or [2], wherein the protective layer has a tensile elongation at break of 800% or more. [4] The unit weight of the protective layer is 40 g / m 2 More than 900g / m 2 A protective film for a blade according to any one of [1] to [3] below. [5] The water vapor permeability of the protective layer is 15.0 g / (m 2 The protective film for a blade according to any one of [1] to [4], wherein the duration is 24 hours or less. [6] A protective film for blades described in any one of [1] to [5], which has an adhesive strength to a SUS plate of 3 N / 10 mm or more. [7] A protective film for a blade according to any one of [1] to [6], having an adhesive strength to a fluororesin layer of 2.5 N / 10 mm or more. [8] A protective film for a blade described in any of [1] to [7], wherein the minimum thickness of the protective film for a blade is 80% or more when the maximum thickness of the protective film for a blade is 100%. [9] A blade for a wind turbine generator having, on its surface, a protective film for a blade according to any one of [1] to [8].

[10] [9] A wind turbine generator comprising a blade as described above. [Explanation of symbols]

[0196] 1 … protective layer 2 … Adhesive layer 10 … Protective film 20 … Blade 30 … Wind power generation equipment

Claims

1. A protective layer containing a polyolefin resin and an adhesive layer disposed on one surface of the protective layer, A protective film for wind power generator blades, wherein the protective layer has a tensile modulus of elasticity of 5 MPa or more and 35 MPa or less.

2. The protective film for blades according to claim 1 , wherein the protective layer has a tensile breaking stress of 5 MPa or more.

3. 2. The protective film for blades according to claim 1, wherein the protective layer has a tensile elongation at break of 800% or more.

4. The unit weight of the protective layer is 40 g / m 2 900g / m or more 2 2. The protective film for blades according to claim 1, wherein:

5. The water vapor permeability of the protective layer is 15.0 g / (m 2 The protective film for blades according to claim 1, wherein the durability is 24 h or less.

6. 2. The protective film for blades according to claim 1, which has an adhesive strength to a stainless steel plate of 3 N / 10 mm or more.

7. 2. The protective film for blades according to claim 1, which has an adhesive strength to the fluororesin layer of 2.5 N / 10 mm or more.

8. 2. The blade protection film according to claim 1, wherein the minimum thickness of the blade protection film is 80% or more when the maximum thickness of the blade protection film is 100%.

9. A blade for a wind turbine generator, having a surface thereof coated with the blade protection film according to any one of claims 1 to 8.

10. A wind turbine generator comprising a blade according to claim 9.

Citation Information

Patent Citations

  • Polyurethane material, method for making such a material, and protective cover for a wind turbine blade

    JP2018503775A

  • Blade and protective laminated sheet for blade

    WO2012102294A1